Implementation Of Nursing Pain Management in Gastritis Patients With Acute Pain in The Emergency - Junaidi Junaidi; Aswin Syahputra; Nana Erika; Riyan Agus Faisal Hasibuan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background:Gastritis is an inflammation of the stomach wall caused by irritation of the gastric mucosa. Gastritis caused by bacterial infections such as Helicobacteri pylory and irritant foods and drinks. The problem posed is acute pain. Nursing interventions to address this problem are pain management. Objective: This case study aims to describe the implementation of nursing pain management in gastritis patients with acute pain. Method: This case study design is a descriptive design in the form of a case study with a nursing care process approach. The case study subjects were 4 patients in the emergency room with the criteria of experiencing gastritis with problems acute pain. This case study was conducted at Muhammadiyah Palembang Hospital on March 16- 23, 2023. The nursing implementation provided was in the form of warm compress and deep breath relaxation to reduce pain in gastritis patients, in patient 1 before the implementation of the pain scale was 5 and fell to 3, the second patient initially had a pain scale of 4 decreasing to 2, in patient 3 the initial scale of 5 was reduced to a scale of 2, and finally patient 4 before the technique was carried out. out the pain scale in patients is 5 after being carried out down to a scale of 3. Using data collection techniques by means of observation, and interviews. Results: The research results describe the need for implementation of pain management (warm compress and deep breath relaxation) to reduce pain in gastritis patients from a moderate pain scale to a mild pain scale.Conclusion:There is an influence in implementing pain management on acute pain in gastritis patients.